Food Safety Implications of Transitions Toward Sustainable Healthy Diets. Issue 2 (December 2020) - Pires, Sara M.; Thomsen, Sofie T.; Nauta, Maarten; Poulsen, Morten; Jakobsen, Lea S.
Despite increased political attention, foodborne diseases still cause a substantial public health, economic, and social burden worldwide. Children younger than 5 years, people living in developing regions, and in the poorest areas of the world are disproportionally affected, bearing a large proportion of the global burden of foodborne disease. Yet, food safety is a prerequisite to ensuring food security globally: Foods that are responsible for important food safety problems are also crucial to ensure food security in some regions and are essential sources of nutrition. Moreover, together with calls for action to meeting international sustainable development goals, global efforts to promote food security and healthy diets have now highlighted the need to modify food systems globally. This article therefore explores the food safety dimensions of transitions toward food systems that promote sustainable healthy diets. The current body of evidence points to the combined health and environmental benefits of shifting toward a more plant-based diet, including vegetables and fruits, nuts, pulses, and whole grains. As a shift toward more plant-based diets may also lead to higher exposures to chemicals or pathogens present in these foods, an evaluation of food safety implications of such transitions is now imperative. We conclude that several synergies between public health, environmental, and food safety strategies can be identified to support dietary transitions.